Spatial Autocorelation of Catch Fisheries Production in East Kalimantan - Erwan Sulistianto; Wahyu Fahrizal; Freddy Maryanto (Jurnal Harpodon Borneo, 2018)
The amount of capture fisheries production in East Kalimantan according to district/city 2016 is a case study in this study. This paper aims to analyze the existence of spatial autocorrelation in capture fisheries production data in East Kalimantan by the district /city in 2016. The method used to analyze global spatial autocorrelation is the Moran Index method and the Local Spatial Autocorrelation (LISA) indicator to analyze spatially automated correlations local. The results of the analysis are automatic spatial correlation of capture fisheries production in East Kalimantan in 2016. The Moran index score obtained is - 0.322304 which indicates that there is a negative autocorrelation or spread pattern and does not have similar characteristics in adjacent locations. Meanwhile, through LISA, it was concluded that there were no significant district/city groupings. Where there is only Berau affected by other regions with a significant value of 0.1%